Periodontal plastic surgery: Made easy with acellular dermal matrix - M Thamilselvan; Prasanta Bandyopathyay; Somen Bagchi; Soma Mallick (Wolters Kluwer Medknow Publications, 2018)
Esthetics has become an important part in periodontal plastic surgery, and soft-tissue architecture plays an important role in achieving it. Among the various techniques, the use of autogenous connective tissue graft has been proved to be an effective and a successful approach in treating gingival recession. Recently, acellular dermal matrix (ADM) allograft has been used as a substitute for palatal connective tissue and it has shown to be a successful alternative for root coverage. This case report is an effort to evaluate the clinical effectiveness of ADM in coverage of denuded root with 6-month follow-up.